Seed quality assurance options for roots, tubers and bananas, including conclusions and recommendations from several cases studies - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The tool was piloted for potato and cassava in Vietnam, cassava in Nigeria and potato in Kenya.